Party system volatility, regeneration and de-institutionalization in Western Europe (1945–2015). (July 2017) - Chiaramonte, Alessandro; Emanuele, Vincenzo
Despite a great flourishing of studies about Latin America and Central and Eastern Europe, the issue of party system institutionalization has been widely neglected in Western Europe, where the presence of stable and predictable patterns of interactions among political actors has been generally taken for granted for a long time. Nevertheless, party system institutionalization is not something that can be gained once and for all. This article proposes a theoretical reconceptualization and a new empirical operationalization of party system (de-)institutionalization. Furthermore, it tests the presence of patterns of de-institutionalization in Western Europe from 1945 to (March) 2015 (336 elections in 19 countries) by using an original database of electoral volatility and of its internal components (regeneration and alteration). Data analysis shows that Western Europe is facing great electoral instability and party system regeneration and that many countries have experienced sequences of party system de-institutionalization, especially in the last two decades.